Evaluation of novel traits influencing the sustainability of the beef industry: greenhouse gas fluxes, feeding and drinking behaviors - Dressler, Elizabeth Anne (Kansas State University, 2022)
Sustainability has recently become an area of increased focus for the beef industry. Feed and water intake behaviors as well as greenhouse gases are novel traits that could impact the sustainability of the beef industry. One of the objectives of this study was to characterize the number of spot samples required to accurately quantify methane, carbon dioxide, and oxygen gas fluxes and metabolic heat production from an individual grazing cow using an open-circuit gas quantification system (OCGQS). One-hundred spot samples from 17 grazing Angus beef cows were used to compute average gas fluxes and metabolic heat production for intervals increasing by 10 visits. The Pearson and Spearman correlations between the full 100 visits and each shortened visit interval were calculated. The recommended number of spot samples needed for the quantification of methane, carbon dioxide, oxygen, and metabolic heat production was 36-38, 40, 38-40, and 36, respectively. Animals in the current study needed 29.5 to 31.8 days to meet the required number of visits for gas fluxes and metabolic heat production. Published literature recommends a similar number of spot samples, however there is a large variation in the average number of visits per day and thus the recommended test duration. For these reasons, protocols for the OCGQS should include the number of spot samples rather than a test duration. Another objective of this study was to estimate the genetic parameters of feed and water intake behaviors. The feed and water intake behavior phenotypes that were calculated include number of sessions (no/d), intake rate (g/s), session size (kg), time per session (s), and session interval (min) from 830 crossbred steers. Feeding behaviors were heritable and ranged from 0.35 to 0.63; drinking behaviors were also heritable and ranged from 0.54 to 0.88. Phenotypic correlations between traits and genetic correlations with DMI or DWI ranged from low to high. A genome-wide association study was performed for each feeding and drinking behavior. Candidate genes and previously reported quantitative trait loci related to feed and water intake were identified. Results indicated that feeding and drinking behaviors are controlled by genetic factors and additional research in this area is needed to determine their role in genetic selection for improved feed and water efficiency.
Keywords: Beef cattle; Greenhouse gases; Methane; Feeding behavior; Drinking behavior; Sustainability